MAINTENANCE SILK WORMS (Tubifex sp) WITH A DOSES OF DIFFERENT FERTILIZERS ON RECIRCULATION SYSTEMS - Selamat Hidayat; Iskandar Putra; Mulyadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Silk worms is one kind of natural food like fish larvae because they contain good nutrients for the growth of fish larvae. This study aims to determine the appropriate amount of fertilizer and the implementation of systems of recirculation to the growth of silk worms. The research was conducted on July 29 to September 18, 2016 placed in a field laboratory of the Faculty of Fisheries and Marine University of Riau. The media used is in the form of sludge reservoirs, dedek smooth, tofu, chicken manure and EM4. While the materials used are silk worms obtained from collectors. Experimental method used was a completely randomized design (CRD) with 3 levels of the factor treatments and 3 repetitions. The treatments used: P0: without the use of chicken manure, P1: 500 g of chicken manure / 0.098 m2, P2: 600 g of chicken manure / 0.098 m2, and P3: 700 g of chicken manure / 0.098 m2. The data observed is the growth of biomass weight, average length, and water quality. The results of this study with the treatment of chicken manure fertilizer of different very significant effect (P <0.05) on the growth of biomass weight of silk worms. Biomass is highest in treatment P3 (700 g chicken manure / 0.098 m2) in 69 g. As for the average length, chicken manure fertilizer does not affect significantly different (P> 0.05). The average length of the highest in treatment P2 (1.83 cm). Water quality measured during the study was the temperature (25-29˚C), pH (6-7), dissolved oxygen (6,0-6,5 ppm), and CO2-free (2,0-3,5 ppm). From this study it can be concluded that giving different chicken manure can affect the growth of silk wormsKey Words : Tubifex sp, sludge reservoirs, chicken manure, biomass, dan average length